P80 The race for Hepatitis C Elimination: a historical review. (20th September 2022) - Botterill, Gemma; Osborne, William; Moore, Angelie; Mutimer, David
Abstract : Viral hepatitis is a major cause of mortality, with an estimated 1.34 million deaths globally per year. The introduction of Direct Acting Anti-virals (DAAs) from 2014, means hepatitis C (HCV) can be cured in >95% of patients (Vine et al, 2015). In 2016, the World Health Organization (WHO) set a target of eliminating viral hepatitis by 2030 (WHO, 2016). National Health Service England (NHSE) took this one step further, planning for elimination across England by 2025. NHSE has made a substantial investment for purchasing medication and supporting case finding. Our team worked in collaboration with Public health England (PHE), now UK Health Security Agency (UKHSA) in a look back exercise to identify undiagnosed patients. In 2018 PHE provided us with details of over 4, 500 patients who were HCV antibody positive between 1996–2017. This was reviewed and cross referenced with our computer systems. Patients, who had been cured, had died and those with planned treatment were removed. For those remaining, GP letters were sent, requesting further information. If a response was not received within four weeks, a letter was sent to the patient directly. From 4538 patients, 1806 records have been reviewed. Of these, PCR data was available in 1, 635 cases. 942 did not need contacting. 693 required GP letters requesting updated results or consent to contact the patient directly. 100 responses were received. Before COVID-19, 212 patient letters were sent, with 25 responses. Many people may not be aware they are infected (Thursz, 2017). Others may be aware but not referred for treatment. Hospitals therefore need to work with GP's to identify potential HCV patients (Public Health England, 2017). Setting up a hospital lab result alert system helps with timely direct referrals. To engage patients a variety of locations for testing and treating may be required; such as remote phlebotomy hubs, drug and alcohol services and local hospitals. As a service we work closely with our local drug and alcohol service, Change, Grow, Live (CGL). This enables us to offer a shortened pathway to testing, treatment and liver staging by Fibroscan. This ongoing project will enable our team to identify those requiring blood tests and potential treatment. As we continue we expect an increase in patient numbers to our CNS clinics. One major limitation is limited access to regional hospital laboratory results. Another limitation is staff being available to review files, responses to letters and chasing blood tests or results. References: Public Health England (2017). Hepatitis C in the UK – 2017 Report.Working to Eliminate Hepatitis C as a Major Public Health Threat . London: PHE. Thursz M. (2017). The fight against hepatitis C has not yet been won: here's what we have to do. Huffington Post; 10 August 2017. Vine LJ et al . Diagnosis and management of hepatitis C. British Journal of Hospital Medicine; 2015;76 :11, 625–630. World Health Organization (2016). Combating Hepatitis B and C to Reach Elimination by 2030. Geneva: WHO.